QUANTITATIVE PHYTOCHEMICAL SCREENING AND TERMICIDAL ACTIVITIES OF EUPHORBIA TIRUCALLI L. EXTRACTS ON DANIELLIA OLIVERI (ROLFE) HUTCH. AND DALZIEL AND FICUS CAPENSIS THUNB. WOODS (FUDMA JOURNAL OF SCIENCES, 2020)
This study investigated effect of Euphorbia tirucalli extracts on Daniellia oliveri and Ficus capensis woods. Wood samples were purchased and processed into 10 cm x 2 cm x 2 cm dimensions, while plant parts collected were oven dried before extraction. E. tirucalli  was screened for phytochemicals. Concentrations of 0.5%, 1% and 2% extracts were prepared by serial dilution. Soligum, methanol and untreated wood samples were used as control. Treated wood samples were laid within 6 x 12 metres field at 1 x 3 metres spacing in a Completely Randomized Design (CRD) in a termitarium and data were taken within 8 weeks. Phytochemical results indicated the presence of alkaloids, phenols, tannins, cardiac glycosides, flavonoids and saponins. Percentage absorption of extracts ranged from 47 - 86 % and 94.00 - 50.67 % in D. oliveri and F. capensis, respectively. Percentage retention of extracts ranged from 10.84 - 2.14 kg/m3 and 11.62 - 7.01 kg/m3 in D. oliveri and F. capensis. Soligum treated wood samples were not attacked throughout the period of study. D. oliveri and F. capensis woods treated with 0.5% E. tirucalli methanol extract were not attached on till the 6th and 8th week respectively. The least percentage weight loss of 5.49 % and 28.32 % were recorded for D. oliveri and F. capensis woods treated with soligum, while, 27.5 5 % and 52.50 % weight loss were recorded for F. capensis and D. oliveri woods treated with 0.5% methanol extract. It was concluded that the use o
Keywords: Weight loss, phytochemicals, absorption, retention, termites, incidence of attack